Investigation on Transient Characteristics of High Pressure Vessel Water Level Measurement - Wang, Meng; Chen, Wenzhen; Fan, Guangming (Frontiers in Energy Research, 2021)
An experimental study is conducted on the characteristics of high pressure vessel water level measurement both at the steady and the transients. The swollen and collapsed water levels are observed experimentally. The test results show that the swollen water level has a relatively fixed difference with the collapsed one for the transient of both high and low depressurization. Under the conditions of steady and heat up, the differences between the swollen and collapsed water level are acceptable. For the transients of depressurization, the outputs from the three channels of the inside vessel double-reference-tube water level system have a deal differences between each other because of the thermal inertia of the two reference tubes and the water levels in the cistern. In the views of nuclear power plant safety and operation, the outside vessel single-reference-tube water level system used in current pressurizer is adequate and the inside vessel double-reference-tube water level system is suggested as an additional reference to monitor the water level in the steam generator.